A novel silicon heterojunction IBC process flow using partial etching of doped a‐Si:H to switch from hole contact to electron contact in situ with efficiencies close to 23%. (8th January 2019) - Sivaramakrishnan Radhakrishnan, Hariharsudan; Uddin, M.D. Gius; Xu, Menglei; Cho, Jinyoun; Ghannam, Moustafa; Gordon, Ivan; Szlufcik, Jozef; Poortmans, Jef
Abstract: We present a novel process sequence to simplify the rear‐side patterning of the silicon heterojunction interdigitated back contact (HJ IBC) cells. In this approach, interdigitated strips of a‐Si:H (i/p + ) hole contact and a‐Si:H (i/n + ) electron contact are achieved by partially etching a blanket a‐Si:H (i/p + ) stack through an SiOx hard mask to remove only the p + a‐Si:H layer and replace it with an n + a‐Si:H layer, thereby switching from a hole contact to an electron contact in situ, without having to remove the entire passivation. This eliminates the ex situ wet clean after dry etching and also prevents re‐exposure of the crystalline silicon surface during rear‐side processing. Using a well‐controlled process, high‐quality passivation is maintained throughout the rear‐side process sequence leading to high open‐circuit voltages (VOC ). A slightly higher contact resistance at the electron contact leads to a slightly higher fill factor (FF) loss due to series resistance for cells from the partial etch route, but the FF loss due to J02 ‐type recombination is lower, compared with reference cells. As a result, the best cell from the partial etch route has an efficiency of 22.9% and a VOC of 729 mV, nearly identical to the best reference cell, demonstrating that the developed partial etch process can be successfully implemented to achieve cell performance comparable with reference, but with a simpler, cheaper, and faster process sequence. Abstract : A novel in situ partial dry etch process sequence for heterojunction interdigitated back contact (HJ IBC) solar cells was developed, based on NF3 /Ar plasma, whereby the doped a‐Si:H on the rear‐side is switched by etching off the exposed p + a‐Si:H (or n + a‐Si:H) and depositing an n + a‐Si:H (or p + a‐Si:H) on top of the remaining intrinsic a‐Si:H from the first passivation stack, without re‐exposing the c‐Si surface. A best efficiency of 22.9%, identical to reference, was achieved with a simpler and faster process.